Physical Performance and Patient-Reported Outcomes Remain Stable at 5 Years After Total Knee Arthroplasty - Pakpoom Ruangsomboon, M.D., M.Sc.; Onlak Ruangsomboon, M.D., M.Sc.; Chirathit Anusitviwat, M.D.; Bheeshma Ravi, M.D., Ph.D., F.R.C.S.C.; Aasis Unnanuntana, M.D., M.Sc. (Arthroscopy, Sports Medicine, and Rehabilitation, 2025)
Purpose: To evaluate changes in physical performance tests (PPTs) and patient-reported outcome measures (PROMs) at baseline, 1 year after total knee arthroplasty (TKA), and a minimum of 5 years after TKA. Methods: We enrolled patients who underwent TKA between 2013 and 2015 performed by a single arthroplasty surgeon at Siriraj Hospital, Mahidol University, Bangkok, Thailand. We evaluated PPTs and PROMs over a minimum 5-year follow-up period to assess changes over time, identified independent factors associated with PPT deterioration, and determined TKA survivorship. Results: The study included 126 participants with a mean age of 77.8 years. The average follow-up time was 7.4 ± 2.3 years. PPTs and PROMs changed significantly over time from baseline. However, the 2-minute walk test and timed up-and-go test results slightly declined after 1 year but did not attain minimal clinically important differences, and PROMs were maintained and showed no clinically significant changes after 1 year. Hospitalizations owing to complex medical conditions or trauma were independently associated with PPT deterioration. There was a 98.8% survivorship rate at 7.6 years. Conclusions: In an Asian population undergoing TKA, PPTs and PROMs are maintained within acceptable ranges for at least 5 years after primary TKA. Trauma or hospitalizations arising from complex medical conditions were found to be associated with functional decline. A combined evaluation of PPTs and PROMs is advocated for a comprehensive assessment of patients after TKA. Level of Evidence: Level III, cohort study.